The Christian interpretations on the nature of heaven"s mandate in late Ming and early Qing dynasties - Xiao, Qinghe (HTS teologiese studies, 2024)
This paper aims to examine in detail the Christian interpretations on the Confucian concept of the nature of the heaven’s mandate [天命之性] during the late Ming and early Qing dynasties from historical and textual perspective. Neo-Confucians of the Song Dynasty interpret the nature of the heaven’s mandate as human nature, believing that heaven endowed humans with reason, known as the heavenly principle [天理]. In the late Ming period, Christian missionaries such as Jesuits in China used Confucian classics to convey Christian thoughts, interpreting the heaven’s mandate as God’s mandate and the nature of the heaven’s mandate as the spirituality bestowed by God, which is equated with the soul. They also used the nature of the heaven’s mandate as a criterion for determining the authenticity of a teaching (religion[教]), asserting that Christianity is the true teaching (religion). Thus, Christianity in the late Ming and early Qing dynasties provides a new interpretation on the nature of the heaven’s mandate and promotes the integration of Christian and Confucian thoughts through this interpretation.Contribution: The paper provides a detailed review of the history of Christian interpretations on the nature of the heaven’s mandate during the late Ming and early Qing dynasties. Currently, there is limited scholarly research on the theological thoughts of Christianity during this period. This study not only enhances the understanding of the new interpretations by Christianity but also aids in comprehending the theological ideas of Christianity during the late Ming and early Qing periods. By reinterpreting Confucian classics, Christianity endowed them with new meanings, offering valuable references for the localisation of Christian theology and the study of cross-cultural exchange.